2017
DOI: 10.1371/journal.pone.0175068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relative efficacy of a couple cognitive-behaviour therapy (CBT) for Premenstrual Disorders (PMDs), in comparison to one-to-one CBT and a wait list control: A randomized controlled trial

Abstract: DesignA randomised control trial (RCT) was conducted to examine the efficacy of couple-based cognitive behaviour therapy (CBT) for Premenstrual Disorders (PMDs), in comparison to one-to-one CBT and a wait-list control.MethodsTriangulation of quantitative and qualitative outcome measures evaluated changes pre-post intervention. Eighty three women were randomly allocated across three conditions, with 63 completing post-intervention measures, a retention rate of 76%.ResultsRepeated measures analysis of variance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
1
20
0
3
Order By: Relevance
“…Furthermore, only specific techniques of cognitive-behavioural therapies were evaluated in the studies, for example positive reframing only [49] or coping skills training [50]. Since 2012, only a few studies of CBT for the treatment of PMDD have been conducted, mainly comparing CBT with other treatments (e.g., one-on-one CBT vs. couple CBT [51], or CBT vs. fluoxetine [9]). These studies confirmed CBT to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only specific techniques of cognitive-behavioural therapies were evaluated in the studies, for example positive reframing only [49] or coping skills training [50]. Since 2012, only a few studies of CBT for the treatment of PMDD have been conducted, mainly comparing CBT with other treatments (e.g., one-on-one CBT vs. couple CBT [51], or CBT vs. fluoxetine [9]). These studies confirmed CBT to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were Australian women who self-identified as PMS sufferers, who were taking part in a study examining the efficacy of a couple psychological therapy for moderate to severe premenstrual distress (which we henceforth define as PMS). Details of the methodology and results of the therapy evaluation are presented elsewhere (Ussher & Perz, 2017). Eighty-three women completed pre-post intervention surveys, and 30 women were interviewed before and after the intervention.…”
Section: Study Descriptionmentioning
confidence: 99%
“…One month post-intervention, the same questions were asked, with a focus on how the intervention has impacted in each of these areas. The interviewer was independent of program delivery, and the interviews were supplementary to the main quantitative evaluation of the therapy (Ussher & Perz, 2017).…”
Section: Study Descriptionmentioning
confidence: 99%
“…[ 25 ] Couple-based CBT interventions may have a greater positive impact on behavioral coping for PMS women, as compared with one-to-one modality. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%